Exploring Stakeholders Awareness of the Relationship between Periodontal Health and Diabetes at City University Ajman: a questionnaire survey study - Latta, Mutaz Jamil; Abdelmagyd, Hossam; Sidheeq, Meharunneesa Aboobacker (Brazilian Dental Science, 2025)
Periodontal inflammation can worsen glycemic control in diabetic patients, while poorly controlled diabetes can increase the severity of periodontal diseases. Despite the clinical significance of this relationship, awareness among the general population and even healthcare providers often remain limited. Objective: This study aims to investigate the level of awareness among stakeholders at City University Ajman (CUA) regarding the relationship between periodontal health and diabetes. Material and Methods: A cross-sectional survey was conducted using a structured questionnaire to gather data from CUA students, faculty, and staff. The questionnaire assessed participants’ knowledge about periodontal diseases, diabetes, and the interrelationship between these conditions. Data were analyzed to determine awareness prevalence and identify significant knowledge gaps. Results: Preliminary findings indicate varying levels of awareness among different stakeholder groups. While a substantial number of participants acknowledged a connection between periodontal health and diabetes, a detailed understanding of the bidirectional relationship and its implications on overall health was less prevalent. Factors such as educational background and professional experience influenced the degree of awareness. Conclusion: The study highlights the need for enhanced educational initiatives at CUA to increase comprehension of the connection between periodontal health and diabetes. Increasing awareness among stakeholders can contribute to better management and prevention strategies, ultimately promoting overall health and wellbeing within the university community. KEYWORDS Awareness; Diabetes mellitus; Glycemic control; Health Literacy; Oral Health; Periodontal disease.